Teaching Ethics to Management Students: A Reflective Inquiry into Character and Moral Development - Occe Luciana (AL-ISHLAH: Jurnal Pendidikan, 2026)
Ethics education in higher education is often delivered as theoretical content, limiting its impact on students’ moral awareness and character development. This study investigates how reflective and experiential teaching strategies can enhance ethical awareness and character formation among management students.This research employed a qualitative reflective approach grounded in the author’s teaching practice in an Ethics course involving approximately 90 third-semester management students at a private higher education institution in Indonesia. Data were derived from teaching journals, classroom observations, students’ reflective writings, records of debates, and a case-based oral examination. The data were analyzed through thematic reflection, involving iterative review, coding of recurring patterns, and interpretation in light of relevant moral education frameworks.The findings revealed four major themes: (1) growth in moral reasoning, as students shifted from intuitive judgments to structured ethical deliberation; (2) increased empathy and perspective-taking through peer dialogue; (3) enhanced engagement and ethical awareness through experiential activities such as film analysis, debates, and role-play; and (4) the effectiveness of case-based oral examinations in revealing students’ ethical reasoning and reflective depth.These findings suggest that ethics education becomes more meaningful when positioned as a reflective and dialogical process rather than a purely theoretical subject. Integrating experiential learning and authentic assessment can support the development of moral reasoning, empathy, and integrity, contributing to more transformative ethics education in management programs.